Exploring Students’ Engagement Perspectives and Overcoming Writing Challenges in Academic Writing Classrooms - Muhammad Deni Irkhamil Maulana; Annisa Jihan Salsabil (Universitas Nusantara PGRI Kediri, 2026)
Technology-based writing pedagogy in higher education plays an important role in fostering a more interactive and collaborative learning environment. However, the extent to which digital platforms promote meaningful student engagement and support students in overcoming academic writing challenges remains underexplored, particularly in English as a Foreign Language (EFL) contexts. Therefore, this study aims to explore students’ engagement in academic writing through the use of Google Docs and to examine how this platform helps address challenges encountered during the writing process. This study employed a qualitative method with a case study approach conducted in a third-semester academic writing class at a university in East Java. Data were collected through questionnaires and semi-structured interviews involving 39 participants. The findings revealed that students perceived Google Docs positively in supporting engagement, motivation, and collaborative productivity during academic writing activities. The platform facilitated active participation, feedback exchange, and collaborative interaction throughout the writing process. However, several challenges were also identified, including maintaining student engagement, supporting more structured and coherent writing, adapting learning practices to digital environments, and managing writing format consistency. These findings suggest that Google Docs can function as a supportive pedagogical tool when integrated with appropriate instructional strategies. This study contributes to a better understanding of how collaborative technology can support student engagement and address writing challenges in EFL higher education contexts.